Social reproduction theory: remapping class, recentering oppression (London, 2017)
"This groundbreaking collection explores the profound power of Social Reproduction Theory to deepen our understanding of everyday life under capitalism. While many Marxists tend to focus on the productive economy, this book focuses on issues such as child care, health care, education, family life and the roles of gender, race and sexuality, all of which are central to understanding the relationship between economic exploitation and social oppression.In this book, leading writers such as Lise Vogel, Nancy Fraser, David McNally and Susan Ferguson reveal the ways in which daily and generational reproductive labour, found in households, schools, hospitals and prisons, also sustains the drive for accumulation. Presenting a more sophisticated alternative to intersectionality, these essays provide ideas which have important strategic implications for anti-capitalists, anti-racists and feminists attempting to find a path through the seemingly ever more complex world we live in."